Prototype Of A Three-Phase Voltage Monitoring System For Induction Motor Protection Based On Arduino Esp32 With Telegram Notifications - Arief Budi Mustofa (CV. AFDIFAL MAJU BERKAH, 2026)
The three-phase electrical power distribution system is the main system widely used in industrial installations, including the Waste Water Treatment Plant (WWTP) at Rasuna Epicentrum, South Jakarta. The voltage stability of each phase significantly affects the performance of induction motors and control systems. This research aims to design and develop a three-phase voltage monitoring prototype system based on the ESP32 microcontroller using the PZEM-004T sensor to detect voltage and current in each phase. The measurement results are displayed on a 2004 Blue Backlight LCD, accompanied by visual and audio indicators in the form of LEDs and a buzzer. In addition, the system is equipped with an automatic notification feature via Telegram Bot, which provides real-time alerts when abnormalities such as overvoltage, undervoltage, voltage unbalance, or phase loss occur. The research method consists of several stages, including literature study, hardware and software design, system assembly, on-site testing at the WWTP, and data analysis. The test results show that the system can measure voltage on each phase with an average error of ±1.8% compared to standard measuring instruments. The system successfully sends Telegram notifications within an average delay of 2.3 seconds after detecting anomalies. Based on the experimental results, the developed system is proven to be accurate, responsive, and efficient for real-time three-phase voltage monitoring. Therefore, this prototype can serve as an alternative IoT-based electrical monitoring system applicable to support operational and maintenance activities in industrial systems such as WWTP.